Hepatic resection vs. transarterial chemoembolization for hepatocellular carcinoma beyond the Milan criteria with portal hypertension. Issue 7 (July 2018) - Yang, Jian; Yang, Jia-Yin; Yan, Lu-Nan; Wen, Tian-Fu; Li, Bo; Wang, Wen-Tao
Abstract: Objective: To assess the value of hepatic resection by comparing it with transarterial chemoembolization for hepatocellular carcinoma beyond the Milan criteria with clinically relevant portal hypertension. Methods: A total of 363 patients and 193 propensity score-matched patients who had hepatocellular carcinoma beyond the Milan criteria with clinically relevant portal hypertension and underwent hepatic resection or transarterial chemoembolization were retrospectively analyzed. The short-term and long-term results were compared. Results: Postoperative complications and 30-day mortality were similar between the two groups. The hepatic resection provided a survival benefit over TACE at 1, 2, 3, and 5 years. Similar results were observed in the propensity score analysis. Five variables were identified as independent prognostic factors: treatment, AFP, Child–Pugh classification, tumor number and extension of disease in a multivariate analysis of the whole study population. In addition, only the tumor number was identified as an independent risk factor after propensity matching. The subgroup analysis demonstrated that the survival benefit of the hepatic resection can only be derived in a subset of patients with a single tumor. Conclusions: In a properly selected group of patients with hepatocellular carcinoma beyond the Milan criteria with clinically relevant portal hypertension, hepatic resection appears to be as safe as TACE and provides a significant survival benefit.